An Interview with Dr. Kimber Thomas, Senior Innovation Specialist with the Connecting Communities Digital Initiative (CCDI) at the Library of Congress - Taylor, Tucker; Thomas, Kimber (Journal of Copyright in Education & Librarianship, 2024)
In this interview, Dr. Thomas discusses the relationship between race and copyright. This conversation with Tucker Taylor of the Journal of Copyright in Education and Librarianship covers Dr. Thomas’s path to copyright education as well as her work at Connecting Communities Digital Initiative (CCDI) at the Library of Congress.  Dr. Thomas details the interaction of race and copyright, and how it relates to librarianship and education.  She also details ideas for librarians and educators to help improve our current situation.